2020
DOI: 10.5539/mas.v14n9p37
|View full text |Cite
|
Sign up to set email alerts
|

School Bullying Behavior among Adolescents in Palestinian Public Schools from their Teachers’ Perspective

Abstract: The purpose of this study was to investigate the school bullying behavior among adolescents in public schools in the Qalqilya Governorate from the teachers’ perspective in the first semester of the academic year (2018-2019). The study sample consisted of (240) teachers from the whole study population, which comprised 1200 teachers from public schools in the Qalqilya Governorate. The researcher used the descriptive research approach. A Questionnaire was used to measure school bullying behaviors. The q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to the study's findings, more than half of the participants say bullying is a moderate problem at their school, while one-quarter believe it is a major problem. That could be because, as the professors have indicated, school is critical in reducing bullying, which I agree with [17]. Most instructors stated that bullying among teens is a very high degree problem in schools, according to those who gave teachers' perspectives on school bullying behavior among adolescents.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…According to the study's findings, more than half of the participants say bullying is a moderate problem at their school, while one-quarter believe it is a major problem. That could be because, as the professors have indicated, school is critical in reducing bullying, which I agree with [17]. Most instructors stated that bullying among teens is a very high degree problem in schools, according to those who gave teachers' perspectives on school bullying behavior among adolescents.…”
Section: Discussionmentioning
confidence: 74%
“…In contrast, a higher percentage of male than female students report being physically bullied (6% vs. 4%) and threatened with harm (5% vs. 3%). Bullied students reported that bullying occurred in the following places: the hallway or stairwell at school (42%), inside the classroom (34%), in the cafeteria (22%), outside the school grounds (19%), on the school bus (10%), and in the bathroom or locker room (9%) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Literature About Bullying and Psychoeducational Interventionmentioning
confidence: 99%